Correlation between the severity of critically ill patients and clinical predictors of bronchial aspiration - Medeiros,Gisele Chagas de (2016)
Objective: To determine whether the severity of non-neurological critically ill patients correlates with clinical predictors of bronchial aspiration. Methods: We evaluated adults undergoing prolonged orotracheal intubation (> 48 h) and bedside swallowing assessment within the first 48 h after extubation. We collected data regarding the risk of bronchial aspiration performed by a speech-language pathologist, whereas data regarding the functional level of swallowing were collected with the American Speech-Language-Hearing Association National Outcome Measurement System (ASHA NOMS) scale and those regarding health status were collected with the Sequential Organ Failure Assessment (SOFA). Results: The study sample comprised 150 patients. For statistical analyses, the patients were grouped by ASHA NOMS score: ASHA1 (levels 1 and 2), ASHA2 (levels 3 to 5); and ASHA3 (levels 6 and 7). In comparison with the other patients, those in the ASHA3 group were significantly younger, remained intubated for fewer days, and less severe overall clinical health status (SOFA score). The clinical predictors of bronchial aspiration that best characterized the groups were abnormal cervical auscultation findings and cough after swallowing. None of the patients in the ASHA 3 group presented with either of those signs. Conclusions: Critically ill patients 55 years of age or older who undergo prolonged orotracheal intubation (≥ 6 days), have a SOFA score ≥ 5, have a Glasgow Coma Scale score ≤ 14, and present with abnormal cervical auscultation findings or cough after swallowing should be prioritized for a full speech pathology assessment.